2022
DOI: 10.3390/ijms23063125
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of Macrophage Activation by the Natural Yolkin Polypeptide Complex from Egg Yolk

Abstract: Ageing is accompanied by the inevitable changes in the function of the immune system. It provides increased susceptibility to chronic infections that have a negative impact on the quality of life of older people. Therefore, rejuvenating the aged immunity has become an important research and therapeutic goal. Yolkin, a polypeptide complex isolated from hen egg yolks, possesses immunoregulatory and neuroprotective activity. Considering that macrophages play a key role in pathogen recognition and antigen presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…This complex at 100 µg/mL possessed the same or even higher cytokine-inducing activity than the lipopolysaccharide (LPS) used as a positive control. Subsequent studies have shown that purified Y polypeptide complex possesses immunomodulatory activity, which was confirmed in the human whole blood (as ex vivo model), mouse bone marrow-derived macrophages of the BMDM cell line, and murine macrophage-like cell line J774.2 (as in vitro models) ( Polanowski et al, 2012 , 2013 ; Zambrowicz et al, 2017 ; Kazana et al, 2020 , 2022a ).…”
Section: Yolkin (Y) Polypeptide Complex From Egg Yolkmentioning
confidence: 84%
See 4 more Smart Citations
“…This complex at 100 µg/mL possessed the same or even higher cytokine-inducing activity than the lipopolysaccharide (LPS) used as a positive control. Subsequent studies have shown that purified Y polypeptide complex possesses immunomodulatory activity, which was confirmed in the human whole blood (as ex vivo model), mouse bone marrow-derived macrophages of the BMDM cell line, and murine macrophage-like cell line J774.2 (as in vitro models) ( Polanowski et al, 2012 , 2013 ; Zambrowicz et al, 2017 ; Kazana et al, 2020 , 2022a ).…”
Section: Yolkin (Y) Polypeptide Complex From Egg Yolkmentioning
confidence: 84%
“…The impact of Y on the secretory activity of the human whole blood ex vivo has been studied most extensively because the use of unseparated whole blood cultures mimicked the natural microenvironment in which the different leukocyte populations (such as TH1 and TH2) and macrophages can cooperate. Y complex purified from IgY was found to efficiently induce pro-inflammatory factors such as interferons α/β ( IFNs α/β ), interleukin 1 beta ( IL-1β ), interleukin 6 ( IL-6 ), chemotactic interleukin 8 (IL-8) and tumor necrosis factor-alpha ( TNF-α ) controlling the cellular immune response, and anti-inflammatory cytokine interleukin 10 (IL-10) ( Polanowski et al, 2012 , 2013 ; Zabłocka et al, 2014 , 2021a ; Kazana et al, 2020 , 2022a ).…”
Section: Yolkin (Y) Polypeptide Complex From Egg Yolkmentioning
confidence: 99%
See 3 more Smart Citations